Fungal-host interactions: insights into microRNA in response to Paracoccidioides species - Singulani, Junya de Lacorte [UNESP]; Silva, Julhiany de Fatima da [UNESP]; Gullo, Fernanda Patricia [UNESP]; Costa, Marina Celia; Fusco-Almeida, Ana Marisa [UNESP]; Enguita, Francisco Javier; Soares Mendes-Giannini, Maria Jose [UNESP] (Fundaco Oswaldo Cruz, 2020)
BACKGROUND Paracoccidioides spp. causes paracoccidioidomycosis (PCM), an important and frequent systemic mycosis that occurs in Latin America. The infectious process begins with contact between the fungus and lung cells, and the molecular pattern of this interaction is currently poorly understood. MicroRNAs (miRNAs) are small non-coding RNAs that regulate the gene expression in many biological processes, including in the infections. OBJECTIVE This study aimed to analyse the expression of miRNAs in lung cells as response to infection by Paracoccidioides spp. METHODS A quantitative real-time polymerase chain reaction (RT-qPCR) based screening was employed to verify differentially expressed miRNAs in human lung cells infected with three different species; Paracoccidioides lutzii, Paracoccidioides americana, and Paracoccidioides brasiliensis. Furthermore, the in silico predictions of target genes and pathways for miRNAs were obtained. FINDINGS The results showed that miRNAs identified in the lung cells were different according to the species studied. However, based on the predicted targets, the potential signaling pathways regulated by miRNAs are common and related to adhesion, actin cytoskeleton rearrangement, apoptosis, and immune response mediated by T cells and TGF-1 beta. MAIN CONCLUSIONS In summary, this study showed the miRNAs pattern of epithelial cells in response to infection by Paracoccidioides species and the potential role of these molecules in the regulation of key pathogenesis mechanisms of PCM.
Keywords: paracoccidioidomycosis; microRNAs; pathways; target genes; lung cells